Determinan Niat Generasi Milenial di Indonesia Menggunakan Kosmetik Halal dengan Literasi Halal sebagai Variabel Moderasi - Durohman, Hapid (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
This research aims to investigate the influence of religious commitment and self-efficacy as internal variables on the purchasing behavior of Halal cosmetics among the Millennial Generation in Indonesia. Additionally, the study examines the moderating role of Halal literacy in the relationships between behavior, subjective norms, perceived behavioral control, and intentions to purchase Halal cosmetics. The research employs a quantitative method with Structural Equation Modeling analysis using SmartPLS 4.0 software. The findings reveal that religious commitment and self-efficacy significantly influence the purchasing behavior of the Millennial Generation regarding Halal cosmetics, and normative beliefs significantly affect subjective norms. Furthermore, attitude and subjective norms exhibit a significant relationship with the intention to purchase Halal cosmetics, while perceived behavioral control does not show significance. Moreover, Halal literacy has a positive moderating effect on behavior and subjective norms concerning the purchase intention. However, halal literacy does not moderate the relationship between perceived behavioral control the purchase intention.